A new skink fauna from Caribbean islands (Squamata, Mabuyidae, Mabuyinae) - Hedges, S. Blair; Conn, Caitlin E. (Zootaxa, 2012)
Neotropical skinks are unique among lizards and other vertebrates in their degree of convergence, in reproductive traits,with eutherian mammals. They have also been famously difficult to classify into species, largely because of a conservativebody plan and paucity of conventional diagnostic characters. Currently there are 26 recognized species, six of which occuronly on Caribbean islands. All are placed in a single genus, Mabuya. We conducted a systematic revision of Neotropicalskinks using both conventional and unconventional morphological characters, supplemented by DNA sequence analyses.We define 61 species grouped into 16 clades, recognized here as genera. They include three available generic names(Copeoglossum, Mabuya, and Spondylurus) and 13 new genera: Alinea gen. nov., Aspronema gen. nov., Brasiliscincusgen. nov., Capitellum gen. nov., Exila gen. nov., Manciola gen. nov., Maracaiba gen. nov., Marisora gen. nov., Noto-mabuya gen. nov., Orosaura gen. nov., Panopa gen. nov., Psychosaura gen. nov., and Varzea gen. nov. These 16 generaof skinks form a monophyletic group and are placed in the Subfamily Mabuyinae of the skink Family Mabuyidae. Sixother skink families are recognized: Acontidae, Egerniidae, Eugongylidae, Lygosomidae, Scincidae, and Sphenomorphi-dae. We describe three new subfamilies of Mabuyidae: Chioniniinae subfam. nov., Dasiinae subfam. nov., and Trachyl-epidinae subfam. nov. We describe 24 new species of mabuyines: Capitellum mariagalantae sp. nov., Capitellumparvicruzae sp. nov., Copeoglossum aurae sp. nov., Copeoglossum margaritae sp. nov., Copeoglossum redondae sp.nov., Mabuya cochonae sp. nov., Mabuya desiradae sp. nov., Mabuya grandisterrae sp. nov., Mabuya guadeloupae sp.nov., Mabuya hispaniolae sp. nov., Mabuya montserratae sp. nov., Marisora aurulae sp. nov., Marisora magnacornaesp. nov., Marisora roatanae sp. nov., Spondylurus anegadae sp. nov., Spondylurus culebrae sp. nov., Spondylurus caico-sae sp. nov., Spondylurus haitiae sp. nov., Spondylurus magnacruzae sp. nov., Spondylurus martinae sp. nov., Spondy-lurus monae sp. nov., Spondylurus monitae sp. nov., Spondylurus powelli sp. nov., and Spondylurus turksae sp. nov. Wealso resurrect 10 species from synonymies: Alinea lanceolata comb. nov., Alinea luciae comb. nov., Capitellum metalli-cum comb. nov., Mabuya dominicana, Marisora alliacea comb. nov., Marisora brachypoda comb. nov., Spondylurusfulgidus comb. nov., Spondylurus nitidus comb. nov., Spondylurus semitaeniatus comb. nov., and Spondylurus spilonotuscomb. nov. Of the 61 total species of mabuyine skinks, 39 occur on Caribbean islands, 38 are endemic to those islands,and 33 of those occur in the West Indies. Most species on Caribbean islands are allopatric, single-island endemics, al-though three species are known from Hispaniola, three from St. Thomas, and two from Culebra, St. Croix, Salt Island,Martinique, the southern Lesser Antilles, Trinidad, and Tobago. Co-occurring species typically differ in body size and be-long to different genera. Three ecomorphs are described to account for associations of ecology and morphology: terrestri-al, scansorial, and cryptozoic. Parturition occurs at the transition between the dry and wet seasons, and the number ofyoung (1–7) is correlated with body size and taxonomic group. Molecular phylogenies indicate the presence of many un-named species in Middle and South America. A molecular timetree shows that mabuyines dispersed from Africa to SouthAmerica 18 (25–9) million years ago, and that diversification occurred initially in South America but soon led to coloni-zation of Caribbean islands and Middle America. The six genera present on Caribbean islands each represent separate dis-persals, over water, from the mainland during the last 10 million years. Considerable dispersal and speciation alsooccurred on and among Caribbean islands, probably enhanced by Pleistocene glacial cycles and their concomitant sea lev-el changes. Based on IUCN Redlist criteria, all of the 38 endemic Caribbean island species are threatened with extinction.Twenty-seven species (71%) are Critically Endangered, six species (16%) are Endangered, and five species (13%) are Vul-nerable. Sixteen of the Critically Endangered species are extinct, or possibly extinct, because of human activities duringthe last two centuries. Several of the surviving species are near extinction and in need of immediate protection. Analysisof collection records indicates that the decline or loss of 14 skink species can be attributed to predation by the Small IndianMongoose. That invasive predator was introduced as a biological control of rats in sugar cane fields in the late nineteenthcentury (1872–1900), immediately resulting in a mass extinction of skinks and other reptiles. The ground-dwelling and diurnal habits of skinks have made them particularly susceptible to mongoose predation.